Analysis of Organization Leadership As An Implementation Strategy Of Performance Of National Social Security Fund, Kenya. - Julius Moenga Matai; Martin Onsiro (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
One of the most important factors that determine the success of business endeavors is the organizational leadership that is both focused and effective. For the purpose of inspiring teams and directing efforts toward the accomplishment of organizational objectives, this leadership is absolutely necessary. The study purpose was to analyze organization leadership as an implementation strategy of performance of National Social Security Fund, Kenya. The researcher identified three theories for the study; Economic Theory of wealth creation, Social cognitive Theory and Systems Theory. The study philosophy was interpretivism with explanatory and descriptive research design espoused. The target population of the study was 365 employees of the National Social Security Fund at the head quarters. The population was stratified or categorized according to their cadres, then purposive sampling was used on the predetermined senior management cadre while simple random sampling techniques was used on the middle management and non-management staff who had equal chances of being selected for analysis. Questionnaires were administered to be completed by respondents for primary data while document analysis helped the researcher to secure secondary data. The sample size was 186 and this was determined using Krejcie and Morgan table. Data was analyzed using inferential and descriptive statistics. Under inferential statistics the researcher used regression while under descriptive statistics; the mean and the standard deviation were used for measures of central tendency and measures of dispersion respectively. The outcome was presented by the use of frequency tables. The study demonstrated a strong positive correlation (R = 0.793) between leadership and performance, with approximately 62.9% of the variability in performance explained by the model (R Square = 0.629). ANOVA results indicated that the regression model is statistically significant (F = 9.168, p < .001), suggesting that leadership contributed to explaining the variability in performance. The coefficient revealed significant influences of leadership on performance (p < .05). Specifically, a one-unit change in each of these factors led to significant percentage changes in NSSF's performance; leadership scoring 0.192 or (19.2%). Based on these results, recommendations were made to enhance organizational effectiveness, leadership programs should be implemented to empower managers and executives, fostering a culture of strong leadership within NSSF. Further studies should explore the mediating role of technology on the influence of strategy implementation processes.